PULMONARY EMBOLISM MANAGEMENT CHALLENGES IN DIAGNOSTIC AND TREATMENT OF 81 YEAR OLD MAN IN THE SETTING OF RURAL AREA WITH LIMITED RESOURCES : A CASE REPORT - Sidhi Laksono; Abigail Siagian (Fakultas Kesehatan Universitas Muhammadiyah Sumatera Barat, 2024)
Background: Pulmonary embolism is a cardiology emergency with a high mortality rate that is hard to diagnose for its symptoms. The adequate diagnosis of pulmonary embolism requires advanced laboratory and imaging facilities which are not widely available in Indonesia. The lack of facilities and pharmacological availability is an important problem for the delay of treatment and diagnosis of pulmonary embolism will increase the mortality number. This case reports on a patient with pulmonary embolism, managed in a limited healthcare facility. Case Illustration: A-81-year-old Man came with sudden dyspnea and hemoptoe. Physical examination showed mild tachycardia, a drop of blood saturation, and signs of right heart failure. His ECG showed deep S wave in lead I, Q wave in lead III (McGinn-white sign), P pulmonary in lead II, III, aVF, inverted T in inferior and anterior lead. Diagnosis were determined by the clinical score and the ECG pattern. The patient showed hemodynamic instability and was included as a high-risk pulmonary embolism, therefore systemic thrombolysis should be the goal therapy for this patient. Due to the unavailability of systemic thrombolysis, systemic anticoagulant therapy using fondaparinux sodium was initiated and hemodynamic support was given. The patient developed refractory shock despite the usage of the hemodynamic support and died after 5 days of hospitalization. Conclusion: The limitation of diagnostic tools and therapy is one of the biggest challenges in rural hospitals for it can increase the mortality rate of PE Patients. The procurement of diagnostic modalities and pharmacology therapies should be carried out in all hospitals in Indonesia to provide the best management for the patient.